ISLAMIC FINANCIAL ETHICS IN MANAGERIAL DECISION-MAKING : A CONCEPTUAL REVIEW OF THE PRUDENTIAL PRINCIPLE IN ISLAMIC FINANCIAL MANAGEMENT - Gusmiarni, Asni; Gusmiarni, Susi; Karyono, Otong (Program Studi Manajemen Keuangan Syariah, 2025)
The rapid development of the Islamic financial industry demands managerial decision-making quality that is not only oriented toward financial performance but also toward compliance with Sharia principles and Islamic ethical values. This article aims to conceptually examine the role of Islamic financial ethics in managerial decision-making by emphasizing the prudential principle in Islamic financial management. The research method employed is a literature review of relevant scientific publications from the last five years concerning Islamic financial ethics, risk management, governance, and managerial decision-making in Islamic financial institutions. The findings indicate that the prudential principle functions not only as a technical risk management instrument but also as a manifestation of the values of trust, justice, moral responsibility, and the protection of wealth (hifz al-mal). However, the implementation of the prudential principle still faces various challenges, such as pressure to achieve performance targets, limitations in human resources, and weak internalization of ethics and Sharia supervision. This article asserts that strengthening Islamic financial ethics and integrating the prudential principle into good governance are fundamental needs to improve the quality of managerial decisions, maintain institutional stability, and realize the sustainability of Islamic financial institutions in line with the objectives of maqasid al-shariah